Optical imaging of collagen fiber damage to assess thermally injured human skin. Issue 6 (21st August 2020) - Schroeder, Alexandra B.; Karim, Aos; Ocotl, Edgar; Dones, Jesús M.; Chacko, Jenu V.; Liu, Aiping; Raines, Ronald T.; Gibson, Angela L. F.; Eliceiri, Kevin W.
Abstract: Surgery is the definitive treatment for burn patients who sustain full‐thickness burn injuries. Visual assessment of burn depth is made by the clinician early after injury but is accurate only up to 70% of the time among experienced surgeons. Collagen undergoes denaturation as a result of thermal injury; however, the association of collagen denaturation and cellular death in response to thermal injury is unknown. While gene expression assays and histologic staining allow for ex vivo identification of collagen changes, these methods do not provide spatial or integrity information in vivo. Thermal effects on collagen and the role of collagen in wound repair have been understudied in human burn models due to a lack of methods to visualize both intact and denatured collagen. Hence, there is a critical need for a clinically applicable method to discriminate between damaged and intact collagen fibers in tissues. We present two complementary candidate methods for visualization of collagen structure in three dimensions. Second harmonic generation imaging offers a label‐free, high‐resolution method to identify intact collagen. Simultaneously, a fluorophore‐tagged collagen‐mimetic peptide can detect damaged collagen. Together, these methods enable the characterization of collagen damage in human skin biopsies from burn patients, as well as ex vivo thermally injured human skin samples. These combined methods could enhance the understanding of the role of collagen in human wound healing after thermal injury and potentially assist in clinical decision‐making.